2014
DOI: 10.5993/ajhb.38.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Blood Levels and Short-term Smoking Reduction with an Electronic Nicotine Delivery System

Abstract: The NJOY® King Bold ENDS delivers nicotine and led to short-term smoking reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 19 publications
3
83
0
1
Order By: Relevance
“…Of these, 13 articles met inclusion criteria for this review [49][50][51][52][53][54][55][56][57][58][59][60][61]. One article reported on the clinical outcomes of interest (two cases of MI) [49].…”
Section: Research Question #2mentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 13 articles met inclusion criteria for this review [49][50][51][52][53][54][55][56][57][58][59][60][61]. One article reported on the clinical outcomes of interest (two cases of MI) [49].…”
Section: Research Question #2mentioning
confidence: 99%
“…One article reported on the clinical outcomes of interest (two cases of MI) [49]. Eleven articles measured heart rate and BP after EC exposure [50][51][52][53][54][55][56][57][58][59][60]. In 5 of these articles, investigators followed participants for at least 1 week [49,[57][58][59][60], but in 7 articles, authors only reported acute outcomes (changes over b 5 h of exposure) [50][51][52][53][54][55][56].…”
Section: Research Question #2mentioning
confidence: 99%
See 3 more Smart Citations